Strategi Kreatif Program Ngaca Bareng Yosi untuk Meregenerasi Audiens di Programa 4 Radio Republik Indonesia - Nadiva Kissi Ananda; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
A radio broadcast program has a unique creative strategy, has an impact on its audience, and has a novelty nature. Radio broadcasting strategies place the listener as the subject and the participants involved to be able to attract the sympathy and involvement of the audience. The purpose of this research is to find out the creative strategy carried out in the Ngaca program with Yosi to regenerate its audience at RRI. This study uses a constructivism paradigm with a descriptive qualitative approach. Creative strategy as a concept. In-depth interviews with selected informants were used to collect data. Source triangulation is used in the validity of this research data. The results of this study explain the creative strategies used in the Ngaca Bareng Yosi program, which are generic from the program itself, preemtive by promoting cultural education, unique selling where broadcasters and music are the strategies, brand image by not changing the inherent Indonesian image.